PENGGUNAAN MODEL PROBLEM BASED LEARNING BY POLYA DALAM MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA PESERTA DIDIK KELAS V SEKOLAH DASAR - Devy Muliawati; Meirza Nanda Faradita; Iswahyuni (Universitas Muhammadiyah Surabaya, 2024)
This research aims to enhance the ability fifth-grade elementary school students to solve mathematical word problems through the implementation of the Problem Based Learning model developed by George Polya. The research methodology employed is Classroom Action Research (CAR), involving 22 students as research subject. Pre-test and post-test instruments were utilized to measure the students' proficiency in solving mathematical word problems. The findings indicate improvement, as evidenced by the average pre-test score in the first cycle, which was 44. 53 with a proficiency level of 4. 5%. In the first cycle, there was an increase in the average score to 71. 71, achieving a proficiency level of 54. 55%. In the second cycle, the average score further increased to 83. 83, with a proficiency level of 86. 36%